Carbon Adsorbent from Waste Materials (Coconut Shell, Oil Palm Shell, Plastic Bag) for Hydrocarbon Gas Storage - Herawan, Safarudin Gazali; Mohamad, Imran Syakir; Mohd Husin, Mohd Haizal; Yusof, Ahmad Anas; Mat Tokit, Ernie (2003)
Coconut shell and oil palm shell are an agricultural waste material found abundantly in Malaysia. Since the characteristics of coconut shell and oil palm shell were found suitable for preparing activated carbon, these materials also have the potential to be prepared into useful and valuable product. Processes have been designed and developed for producing carbon adsorbent using these materials, which is suitable for hydrocarbon gas storage. The proposed work involves processing of carbon adsorbent with different optimal processing systems and also compares with commercial activated carbon. A gas detector for hydrocarbon gas is used for determining the performance of carbon adsorbent that placed in a single column bed. The invention has shown the great feasibility of using this carbon adsorbent for hydrocarbon gas storage, which are applicable and useful in the storage technology such as vehicle fuel storage. This research work will attempt to find a suitable solution to solve the environmental problems by utilizing the waste materials and to look into the industrial aspect of adsorption process for gas storage.